Evaluating the Efficiency of Clarifier Returned Sludge with Poly-aluminum Chloride Coagulant (PAC) for Improving the Removal of Turbidity, COD and PVC - Sara Kahvaei; Afshin Takdastan; Reza Jalilzadeh Yengejeh (Shiraz University of Medical Sciences, 2021)
Background: Nowadays, the discharge of effluents containing chemicals through manufacturers or consumer industries causes major environmental problems. In this study, we assessed the effect of sludge reversal of the clarifier unit on enhancing the coagulant performance of Poly-Aluminum chloride in the removal of turbidity/COD/PVC from PVC effluent of Bandar Imam Khomeini petrochemical plant and reduction of the amount of coagulant and costs.   Methods: The experiments were carried out by Jar test with poly aluminum chloride (PAC); the returned sludge, as the assisting coagulant, and the amplitude of the differentiates including (5.5-11) pH of coagulant concentration (10-140mg/L) and concentration of returned sludge (2-20 ml) were investigated. To ensure the accuracy and precision, we repeated each stage of the experiment three times.   Results: The results showed that the most optimal conditions for coagulant were at pH=8 and the optimum dose of poly aluminum chloride was 25 mg/L plus 5ml of the clear sludge volume in the clarifier. The removal efficiency of turbidity, COD, and PVC under optimum conditions of Poly-Aluminum chloride were reported 99.71%, 97.19%, and 99.55%, respectively.   Conclusion: The results indicated that the sludge of the clarifier, as the main assisting coagulant,  in addition to increasing the efficiency of  the removal turbidity of COD and PVC reduced the dose of the main coagulant.